2014
DOI: 10.1627/jpi.57.164
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Hydrothermal Pretreatment of Eucalyptus and Oil Palm Empty Fruit Bunch for Ethanol Fermentation

Abstract: Effective energy production from lignocellulosic biomass is one of the most important research topics to employing biomass as a widely used energy source. Using hydrothermal pretreatment, ethanol can be effectively produced from the lignocellulosic biomass. However, the effects of using different feedstock species on ethanol production have not yet been elucidated. In this study, eucalyptus and oil palm empty fruit bunch were selected for hydrothermal pretreatment, followed by enzymatic hydrolysis and ethanol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Moreover, the acidic nature of water at elevated temperatures might contribute to the breakdown of OPEFB into other compounds. This aligns with previous studies on hot-compressed water pre-treatment of OPEFB [20].…”
Section: Hydrothermal Pre-treatment Of Opefb On Total Soluble Sugar 3...supporting
confidence: 92%
“…Moreover, the acidic nature of water at elevated temperatures might contribute to the breakdown of OPEFB into other compounds. This aligns with previous studies on hot-compressed water pre-treatment of OPEFB [20].…”
Section: Hydrothermal Pre-treatment Of Opefb On Total Soluble Sugar 3...supporting
confidence: 92%
“…The hydrolysis reaction was conducted using crystalline cellulose (1 g) in an aqueous sodium acetate buffer solution (60 mL), as Matsumura et al reported that real biomass samples (e.g., eucalyptus and palm oil empty fruit bunch) exhibited different glucose production characteristics 1) . As such, a fundamental study employing pure cellulose is carried out herein.…”
Section: General Experimentalmentioning
confidence: 99%
“…In this context, lignocellulosic materials from agricultural and forest residues, such as rice straw, sawdust, and palm oil empty fruit bunch, have attracted growing attention as alternative feedstocks for bioethanol production, as they are both abundant and unutilized 1) . In the case of lignocellulosic materials, the cellulose present in these materials can be hydrolyzed to give glucose, which can then be employed as a substrate for ethanol fermentation.…”
Section: Introductionmentioning
confidence: 99%